Alendronate functionalized PLGA based nanoparticles for the effective treatment of osteoporosis-Formulation to in-vitro release kinetic studies - Pathak, Sandhya; Shukla, Sandeep; Patel, Bharat; Tripathi, Satyendra Kumar; Pandey, Archna (European Journal of Chemistry, 2022)
Osteoporosis is a bone disease caused due to the reducing bone mineral density. Porous and more fragile bones increase the risk of fractures. Hip, spine, shoulder, and wrist bones are commonly affected by osteoporosis. Low bone density is a leading cause of osteoporosis. The most efficient prescribed drugs for the treatment of osteoporosis are bisphosphonates drugs. Alendronate was the first FDA approved bisphosphonate drug for the treatment of osteoporosis. Osteoclast cells are the primary targeting site for alendronate, responsible for bone resorption. A biopharmaceutical classification system class III bisphosphonate acts as a potent, efficient, and bone resorption inhibitor drug. In the present study, alendronate functionalized PLGA based nanoparticles were developed by a solvent diffusion method and optimized for different process variables. The formulated nanoparticles were characterized for surface morphology, particle size distribution, surface charge and drug-polymer compatibility. The scanning electron microscopy and transmission electron microscopy results showed nanoparticle size in the range below 200 nm. The average particle size and zeta potential of the formulated nanoparticles were found to be 175.3 nm and -13.98 mV, respectively. The highest encapsulation efficiency was 65.23%. The release profile was dissolution medium dependent and followed by the Higuchi model of release kinetics.